Phytoplankton blooms associated with upwelling at Cabo Catoche. (15th February 2019) - Reyes-Mendoza, Oscar; Herrera-Silveira, Jorge; Mariño-Tapia, Ismael; Enriquez, Cecilia; Largier, John L.
Abstract: In this work, the spatial and temporal implications of the Non-Eastern Boundary Upwelling (Non-EBUS) on the bio-productivity from coastal shallow waters have been studied. At the coast of Cabo Catoche, on the Yucatán shelf, two 12-day field campaigns (April and July) were conducted. Cross-shore CTD-fluorescence profiles, water samples, and plankton were collected each day. Nutrients, ocean temperature and currents times series from two moorings (8 and 12 m depth) were analyzed, as were temperature and chlorophyll (Chl-a) from satellite data. The water masses from the Yucatan channel reached the coast of Cabo Catoche in both study periods. The Yucatan Upwelling Water (YUW, ~ 19.6–22.5 °C) supplied the surface and subsurface water, up to 6 km offshore, with nutrients during the upwelling pulses from 2 to 5 days. Nutrients were higher in April (nitrate, ammonium < 5, 18 μmol L −1 ), but the phytoplankton bloom was more consistent in July (Chl-a mean, 1.45 mg m −3 ) showing greater distribution across the coast. The steady upwelling plume (cold water, high nutrients) recorded in Cabo Catoche and observed on the north shelf, could have been the result of dynamic uplift in the Yucatan Channel prior to the field campaign. Through the way to the shelf, the plankton increased, explaining the high temporal association between low temperatures and the phytoplankton bloom at the coast. The Non-EBUS has strong implications for the pelagic ecosystem from Cabo Catoche, enhancing productivity and triggering energy flow by the physical process. Highlights: The slope water intrusion pulses create phytoplankton bloom events on few days. The slope water intrusion pulses have implications closer to the Cabo Catoche shore. The physical-biological interactions are by short periods at the pelagic ecosystem.